METHODS OF ENDURANCE DEVELOPMENT IN YOUNG FOOTBALL PLAYERS (American Journal of Interdisciplinary Research and Development, 2022)
Football is the most popular game in the whole world. Football does not stand still, it is continuously developing. The best domestic and foreign football theorists and practitioners continue to search for more and more new variants of games, systems of training processes. The best of the basic tactical training processes are immediately adopted by the leading teams of the world. It is necessary to constantly improve the training process, and most importantly – to plan it correctly.